Efeitos do freio magnético sobre a distribuição da rotação estelar - Silva Sobrinho, Rodrigo da (2015)
The pioneering work proposed by Skumanich (1972) has shown that the projected mean rotational velocity < v sini > for solar type stars follows a rotation law decreases with the time given by t −1/2 , where t is the stellar age. This relationship is consistent with the theories of the angular momentum loss through the ionized stellar wind, which in turn is coupled to the star through its magnetic field. Several authors (e.g.: Silva et al. 2013 and de Freitas et al. 2014) have analyzed the possible matches between the rotational decay and the profile of the velocity distribution. These authors came to a simple heuristic relationship, but did not build a direct path between the exponent of the rotational decay (j) and the exponent of the distribution of the rotational velocity (q). The whole theoretical scenario has been proposed using an efficient and strong statistical mechanics well known as non-extensive statistical mechanics. The present dissertation proposes effectively to close this issue by elaborating a theoretical way to modify the q-Maxwellians’ distributions into q-Maxwellians with physics links extracted from the theory of magnetic braking. In order to test our distributions we have used the GenevaCapenhagen Survey data with approximately 6000 F and G field stars limited by age. As a result, we obtained that the exponents of the decay law and distribution follow a similar relationship to that proposed by Silva et al. (2013).